CURRENT TOOLS FOR MANAGING SOCIAL DEVELOPMENT OF LARGE COMPANIES’ PERSONNEL - T. V. Suvalova; P. O. Masyukova (Вестник университета)
The aim of the study is to analyse the effectiveness of personnel social development management tools. The essence of social policy, social guarantees, social programs has been considered in the article. The importance of managing social development of personnel for large companies has been substantiated, the functions and tasks of social management have been highlighted. The implementation of the functions considered will help to attract and retain more qualified and talented employees, improve the effectiveness of professional interaction in the team and, accordingly, increase the efficiency of the staff and the enterprise as a whole.The influence of the level of planning social programs on increasing the level of employee loyalty to the organization, the growth of labor productivity, social activity, creativity, rationalization of activities have been noted. The role of management of the personnel social development, the social working conditions and social infrastructure has been argued. The most important tools for managing social development of enterprise personnel have been highlighted.